Disruptions to youth contraceptive use during COVID-19: Mixed-methods results from Nairobi, Kenya - Shannon N. Wood; Rachel Milkovich; Mary Thiongo; Peter Gichangi; Meagan E. Byrne; Bianca Devoto; Philip Anglewicz; Michele R. Decker (Public Library of Science (PLoS), 2023)
Ensuring access to sexual and reproductive health (SRH) services for adolescents is a global priority, given the detrimental health and economic impact of unintended pregnancies. To examine whether and how COVID-19 affected access to SRH services, we use mixed-methods data from young men and women in Nairobi, Kenya to identify those at greatest risk of contraceptive disruptions during COVID-19 restrictions. Analyses utilize cross-sectional data collected from August to October 2020 from an existing cohort of youth aged 16-26. Unadjusted and adjusted logistic regression examined sociodemographic, contraceptive, and COVID-19-related correlates of contraceptive disruption among users of contraception. Qualitative data were collected concurrently via focus group discussions (n = 64, 8 groups) and in-depth interviews (n = 20), with matrices synthesizing emergent challenges to obtaining contraception by gender. Among those using contraception, both young men (40.4%) and young women (34.6%) faced difficulties obtaining contraception during COVID-19. Among young men, difficulty was observed particularly for those unable to meet their basic needs (aOR = 1.60; p = 0.05). Among young women, risk centered around those with multiple partners (aOR = 1.91; p = 0.01), or who procured their method from a hospital (aOR = 1.71; p = 0.04) or clinic (aOR = 2.14; p = 0.03). Qualitative data highlight economic barriers to obtaining contraceptives, namely job loss and limited supply of free methods previously available. Universal access to a variety of contraceptive methods during global health emergencies, including long-acting reversible methods, is an essential priority to help youth avert unintended pregnancies and withstand periods of disruptions to services. Non-judgmental, youth-friendly services must remain accessible throughout the pandemic into the post-COVID-19 period.